2016
DOI: 10.19173/irrodl.v17i3.2253
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Students’ Behavioral Intention to Use LMS at a Turkish Post-Secondary Vocational School

Abstract: There is a substantial increase in the use of learning management systems (LMSs) to support teaching and learning activities in higher education institutions. Despite their benefits, students use them to a limited extend due to a number of factors influencing behaviors. This study executed a three-tier use model to examine the predictors of students' behavioral intention to use LMSs at a two-year postsecondary military school in Turkey, and the participants consisted of 155 students. The data were collected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 46 publications
7
46
1
1
Order By: Relevance
“…and is considered as one of the key determinants of IT usage. A study conducted by Subramanian [28] revealed that PU had significant correlation towards behavioral intention of users particularly in adopting elearning technology which was later confirmed by other researchers such as Fu, Farn & Chao [29], Norazah, Ramayah & Norbayah [30], Tarhini, Hone & Liu [31] and Cigdem & Ozturk [16] whereas their studies, conducted in different educational settings and programs, shown that BI was largely driven by PU. Another case in Nigeria that used PU to model Learning Information System (LIS) students' intention to adopt e-learning technology revealed that PU is one of the strongest predictors with empirical support in determining whether a student will accept the e-learning technology or not [32].…”
Section: B Perceived Usefulness (Pu)mentioning
confidence: 62%
See 2 more Smart Citations
“…and is considered as one of the key determinants of IT usage. A study conducted by Subramanian [28] revealed that PU had significant correlation towards behavioral intention of users particularly in adopting elearning technology which was later confirmed by other researchers such as Fu, Farn & Chao [29], Norazah, Ramayah & Norbayah [30], Tarhini, Hone & Liu [31] and Cigdem & Ozturk [16] whereas their studies, conducted in different educational settings and programs, shown that BI was largely driven by PU. Another case in Nigeria that used PU to model Learning Information System (LIS) students' intention to adopt e-learning technology revealed that PU is one of the strongest predictors with empirical support in determining whether a student will accept the e-learning technology or not [32].…”
Section: B Perceived Usefulness (Pu)mentioning
confidence: 62%
“…These hypotheses were merely a confirmation in the Philippine setting since lots of researchers [64][65][66][67], [40], [36], [31], [15], [16] have already concluded that PU and PEOU are two of the strongest determinants of BI. The findings were also supporting previous literature [22], [65], [36], [15] which stated the positive relationship between PEOU and PU (β = .458, p < .01) as hypothesized in H6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicollinearity assumption was tested in order to the existence of multicollinearity among the variables in the analyses. This happened when a high level of correlation of (r>.90) between two or more variables (Cigdem and Ozturk, 2016). Table 3 shows the results for all variables fitted in the suggested criteria with the correlation values ranging from .79 to .90 therefore, discriminant validity was achieved at the item and variable level.…”
Section: Discriminant Validity Of Constructsmentioning
confidence: 95%
“…Moreover, Rudposhti, Zahedfar and Abadi (2016) indicated that behavioral intention can influence users to accept the use of technology. Moreover, Cigdem and Ozturk (2016) explored that self-efficacy is influential factor to determine and predict behavioral intention to accept the use of technology. Therefore, this is shows that behavioral intention can influence lecturer to use ICT.…”
Section: Behavioral Intentionmentioning
confidence: 99%